PENGUKURAN DAN PERBAIKAN TOTAL PRODUCTIVE MAINTENANCE (TPM) MENGGUNAKAN OVERALL EQUIPMENT EFFECTIVENESS (OEE) DAN ROOT CAUSE FAILURE ANALYSIS (RCFA) - Amrussalam, Amrussalam; Santoso, Purnomo Budi; Tama, Ishardita Pambudi (Industrial Engineering Department, Faculty of Engineering, Universitas Brawijaya, 2016)
Total productive Maintenance (TPM) is an initiative to optimize the effectiveness of manufacturing equipment which the objectives are elimination of all accidents, defects and downtimes [5]. The fundamental measurement of TPM using a method called the Overall Equipment Effectiveness (OEE). The study was began by root cause identification of losses using Root Cause Failure anaysis (RCFA), OEE was calculated based on the metrics calculation which consist of availability metrics, performance metrics, and quality metrics, while reliability was calculated based on the value of MTBF.It is followed by recommendation of TPM for improvement of losses . The results of this study indicate that the value of OEE is not achieve of world-class standards, where OEE is only 35,38%. The factor witch greatly affects of poor OEE and reliability is downtime loss in the machine, which is 2394,8 sec / process / day or 88,07% of all total losses. The proposed improvements of losses are application of Autonomous Maintenance and 5S concept, making of the preciseprocess operating standard based on the machine conditions, need for planned maintenance, focused improvement, quality maintenance and most important, supervision of the machine operator.